Code-Switching in Focus: The Standpoints of Language Learners in an ESL Classroom - Lindbergh R. Aquino (SEAMEO QITEP in Language, 2022)
This study was conducted to determine how second-language classrooms regarded code-switching and to look into the relationship between code-switching in their academic performance and attitudes in English language classes. In order to provide statistical analysis for code-switching without modifying the study variable, the study adopted a correlational research method that collected quantifiable data. 124 Grade 11 seniors from the LagunaIsabela Campus of the University of Perpetual Help System who were enrolled during the academic year 2021–2022 made up the study’s sample. The adopted questionnaire was used by the researchers and slightly modified to fit the needs of the study. It was then taken through pilot testing to assess its reliability and consistency, and the respondents responded using Google Forms. The study found no statistically significant differences in the attitudes of the respondents who were grouped according to their strands using Frequency and Percentage, ANOVA, weighted mean, and Pearson correlation. This study also showed that the respondents’ attitudes did not impact their academic performance in English. The majority of respondents represented the STEM strand. The respondents shared the same opinions regarding code-switching and its justifications. When code-switching was used, most of the respondents had excellent academic achievement in English. Their strands had little impact on the respondents’ attitudes. Academic achievement has little impact on the attitudes of the respondents. Additionally, based on the findings of this study, code-switching can be seen as a beneficial teaching and learning approach.